Spoilage pattern of Alumahan (Rastrelliger faughni, Matsui) stored in ice - Estrada, Myrna H.; Acevedo, Teresita P. (1983.)
The spoilage pattern of Faughn's mackerel (Rastrelliger faughni, Matsui) caught off the east coast of the Philippines during ice storage was investigated. Fish were rejected by trained taste panelists after 14-15 days in ice. Inosine monphosphate (IMP) was the main ATP-breakdown product up to the 10th day of storage, followed by inosine and hypoxantine (Hx). Chemical indices of quality correlated significantly with the storage time. At rejection, the K-=values were 67%, Hx levels were around 1.1 uM/g, IMP concentrations were umole/g and % IMP levels were 36%. Trimethylamine and total volatile nitrogen levels served only as indicators of spoilage and did not correlate with storage time. Microbial tests showed good correlation with storage time. Total viable counts and H2S producers count at rejection were 10^7-10^8 cfu/g.
Thesis (MS Food Science)--University of the Philippines Diliman.
Keywords: Alumahan (Fish).; Fishery products -- Spoilage